x → 0 lim ( 1 + x ) x x x 1
Find the closed form of the limit above to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
first , we need to prove that if x → 0 lim e f ( x ) exists then x → 0 lim e f ( x ) = e x p [ x → 0 lim f ( x ) ]
second , i dont know why this true x → 0 lim x x x − 1 = x ( x → 0 lim x x − 1 ) ? i mean what theorem,lemma or definition use to get it...thanks before.
Log in to reply
First, I was using the second method of link : x → a lim ( g ( x ) f ( x ) ) h ( x ) = exp ( x → a lim h ( x ) ( g ( x ) f ( x ) − 1 ) ) for solving 1 ∞ . I can't find the proof.
Second, I was assuming x → 0 lim x x x − 1 = x → 0 lim x x = 1 . Again no reference.
Used second formula to get to answer
When you substitute ( I suppose) lim x → 0 [ x x − 1 ] then simultaneously it converts to a 0 0 not x 0 , thus describing it zero seems inappropriate. Correct me if I took it wrong..
Log in to reply
If we consider x → 0 lim x x = x → 0 lim exp ( x ln x ) . By L'Hôpital's Rule x → 0 lim x ln x = 0 , therefore, x → 0 lim x x = e 0 = 1
x → 0 lim ( 1 + x ) x x x 1 = x → ∞ lim ( 1 + x 1 ) x 1 x 1 x 1 = x → ∞ lim ( 1 + x 1 ) x = e ≈ 2 . 7 1 8 2 8
are you sure that is a rigorous argument?
Log in to reply
This solution is wrong. All of the steps are unjustified.
x → 0 lim ( 1 + x ) x x x 1 = x → ∞ lim ( 1 + x 1 ) x 1 x 1 x 1 1 or equals x → ∞ lim ( 1 + x 1 ) x x x ?
Log in to reply
EDITED. Thanks!
Log in to reply
thats different too .
Log in to reply
@Uzumaki Nagato Tenshou Uzumaki – wolfram alpha check. Did that solve your query?
Nice way of solving it.
I do not think that x^x^x is defined for x < 0 . So the limit should be for x tending to 0+. And as per the solution, I used @Chew-Seong Cheong method.
Problem Loading...
Note Loading...
Set Loading...
L = x → 0 lim ( 1 + x ) x x x 1 = exp ( x → 0 lim x x x 1 ( 1 1 + x − 1 ) ) = exp ( x → 0 lim x x x x ) = exp ( x → 0 lim x x x − 1 1 ) = exp ( 1 1 ) = e ≈ 2 . 7 1 8 A 1 ∞ case, see note. x → 0 lim x x − 1 = 0
Note: For a 1 ∞ case (method 2) : x → a lim ( g ( x ) f ( x ) ) h ( x ) = exp ( x → a lim h ( x ) ( g ( x ) f ( x ) − 1 ) )